2022
DOI: 10.1177/08959048221087206
|View full text |Cite
|
Sign up to set email alerts
|

Segregation, Diversity, and Pathology: School Quality and Student Demographics in Gentrifying New York

Abstract: Discussions of school integration often contrast the perceived deficits of segregated schools with the perceived strengths of schools with diverse student bodies. In this study, I examine the relationships that school community members infer between student demographics and school quality in diversifying areas of New York City. I use portraits of three New Yorkers to examine the ways that school community members reluctantly re-inscribe the stigma associated with segregated schools, assuming that the best way … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The advantaged parents we spoke to, across racial and ethnic identities, either implicitly or explicitly associated academic success with White children and children from middle- or upper-class families. While these parents were often critical of the segregation that had occurred with screened admissions, many nonetheless perpetuated its logic of pathology and assumed that poor, mostly Black and Latinx students who received priority in the new weighted lottery system were less academically capable or prepared, and that schools that continued to enroll large majorities of Latinx students were less academically rigorous (Freidus, 2022 ). For some, class was a way to avoid speaking directly about race or ethnicity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The advantaged parents we spoke to, across racial and ethnic identities, either implicitly or explicitly associated academic success with White children and children from middle- or upper-class families. While these parents were often critical of the segregation that had occurred with screened admissions, many nonetheless perpetuated its logic of pathology and assumed that poor, mostly Black and Latinx students who received priority in the new weighted lottery system were less academically capable or prepared, and that schools that continued to enroll large majorities of Latinx students were less academically rigorous (Freidus, 2022 ). For some, class was a way to avoid speaking directly about race or ethnicity.…”
Section: Resultsmentioning
confidence: 99%
“…By portraying education as a good to be procured in a market, school choice often exacerbates educational segregation and inequality, as parents are asked to seek out what they think is best for their children as individuals, rather than as part of a larger community (Chingos & Monarrez, 2020 ). School choice models can particularly undermine common good notions of education in gentrifying urban districts, as researchers have found that choice policies intended to attract and retain White and other middle and upper middle class families often: reinforce inequitable access to information (André-Bechely, 2005 ; Pattillo, 2015 ); reify parents’ racialized school preferences (Billingham & Hunt, 2016 ; Evans, 2021 ; Hailey, 2022 ); promote opportunity hoarding (Sattin-Bajaj & Roda, 2020 ; Roda & Wells, 2013 ); and accelerate the gentrification process itself (Freidus, 2022 ; Makris, 2015 ; Quarles & Butler, 2018 ).…”
Section: Theoretical Frames: Interest Convergence Meets the Marketmentioning
confidence: 99%
See 2 more Smart Citations
“…Educational policy actors can (strategically or not) mobilize different notions of equity to support and advance their policy goals (Bertrand et al, 2015;Bulkley, 2013;Horsford, 2016;Scott 2013a). Notions of equity can be harnessed or co-opted to support inequitable and unjust policies, reinforce or advance racist and classist ideas such as deficit-thinking and the denial of systemic racism, divert attention from structural inequity, and allow policymakers to characterize themselves in a positive manner as addressing inequity (Bertrand, et al, 2015;Freidus, 2022;Lewis-Durham, 2020;Melamed, 2011;Omi & Winant, 2015;Turner, 2020b). For these reasons, how we conceptualize in/equity has crucial implications for education research and policy.…”
Section: Conceptions Of Equity In Education Policymentioning
confidence: 99%